2018
DOI: 10.1111/dme.13603
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes UK evidence‐based nutrition guidelines for the prevention and management of diabetes

Abstract: A summary of the latest evidence-based nutrition guidelines for the prevention and management of diabetes is presented. These guidelines are based on existing recommendations last published in 2011, and were formulated by an expert panel of specialist dietitians after a literature review of recent evidence. Recommendations have been made in terms of foods rather than nutrients wherever possible. Guidelines for education and care delivery, prevention of Type 2 diabetes, glycaemic control for Type 1 and Type 2 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
214
1
53

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 283 publications
(274 citation statements)
references
References 6 publications
6
214
1
53
Order By: Relevance
“…So, finding an approach that works for each individual is key,’ says Mr McArdle, a member of the committee that developed the 2018 guidelines. For example, individualised dietary approaches should prioritise eating more foods that support good health such as wholegrains, fruit and vegetables, fish, nuts and legumes (pulses), and less red and processed meat, refined carbohydrates and sugar‐sweetened beverages …”
Section: The Need For New Guidancementioning
confidence: 99%
See 3 more Smart Citations
“…So, finding an approach that works for each individual is key,’ says Mr McArdle, a member of the committee that developed the 2018 guidelines. For example, individualised dietary approaches should prioritise eating more foods that support good health such as wholegrains, fruit and vegetables, fish, nuts and legumes (pulses), and less red and processed meat, refined carbohydrates and sugar‐sweetened beverages …”
Section: The Need For New Guidancementioning
confidence: 99%
“…The guidelines suggest that people who want to lose weight to reduce their risk of T2D should restrict energy intake, eat less total and saturated fat, and increase their fibre intake and exercise. Further studies, however, need to identify the most effective dietary intervention to promote weight loss …”
Section: The Need For New Guidancementioning
confidence: 99%
See 2 more Smart Citations
“…The most important feature is that carbohydrate intake and insulin doses should be matched. 35 Adults with type 1 diabetes should not routinely be advised to follow a low glycaemic index diet. 38 A prospective randomised controlled trial found no clinical benefit of a low glycaemic index diet versus a high glycaemic index diet.…”
Section: Self Monitoring Of Blood Glucose and Ketonesmentioning
confidence: 99%